Pass the salt: physiological consequences of ecologically relevant hyposmotic exposure in juvenile gummy sharks ( Mustelus antarcticus ) and school sharks ( Galeorhinus galeus ) - Morash, AJ; Mackellar, SRC; Tunnah, L; Barnett, DA; Stehfest, KM; Semmens, JM; Currie, S (Conservation Physiology, 2016)
Estuarine habitats are frequently used as nurseries by elasmobranch species for their protection and abundant resources; however, global climate change is increasing the frequency and severity of environmental challenges in these estuaries that may negatively affect elasmobranch physiology. Hyposmotic events are particularly challenging for marine sharks that osmoconform, and species-specific tolerances are not well known. Therefore, we sought to determine the effects of an acute (48 h) ecologically relevant hyposmotic event (25.8 ppt) on the physiology of two juvenile shark species, namely the school shark ( Galeorhinus galeus ), listed by the Australian Environmental Protection and Biodiversity Conservation Act as conservation dependent, and the gummy shark ( Mustelus antarcticus ), from the Pittwater Estuary (Australia). In both species, we observed a decrease in plasma osmolality brought about by selective losses of NaCl, urea and trimethylamine N-oxide, as well as decreases in haemoglobin, haematocrit and routine oxygen consumption. Heat-shock protein levels varied between species during the exposure, but we found no evidence of protein damage in any of the tissues tested. Although both species seemed to be able to cope with this level of osmotic challenge, overall the school sharks exhibited higher gill Na+/K+-ATPase activity and ubiquitin concentrations in routine and experimental conditions, a larger heat-shock protein response and a smaller decrease in routine oxygen consumption during the hyposmotic exposure, suggesting that there are species-specific responses that could potentially affect their ability to withstand longer or more severe changes in salinity. Emerging evidence from acoustic monitoring of sharks has indicated variability in the species found in the Pittwater Estuary during hyposmotic events, and together, our data may help to predict species abundance and distribution in the face of future global climate change.